International Conference on Computer and Communication Engineering (ICCCE'10) 2010
DOI: 10.1109/iccce.2010.5556752
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic radiation from mobile phone near ear-skull region

Abstract: Mobile phones produce radio frequency signal that is transferred as Electromagnetic radiation (EMR). EMR has the ability to penetrate through semi solid substances especially human body's tissues and caused dielectric heating. This effect can be classified as thermal and non thermal radiation. The skin near ear skull region is very thin compare to other part of human body. When using mobile phone for a longer period of time, this area absorbs EMR easily that can affects human immune systems. This effect result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Emissions of thermal radiation was also proven to be much lower with Bluetooth headsets than cellphones as described in Mat et al's (2010) study. Cellphone and Bluetooth headset emissions of thermal radiation were analyzed and compared using a thermal imaging camera; this camera captured the local temperature around the ear-skull region.…”
Section: Bluetooth Hands-free Headsetssupporting
confidence: 52%
See 1 more Smart Citation
“…Emissions of thermal radiation was also proven to be much lower with Bluetooth headsets than cellphones as described in Mat et al's (2010) study. Cellphone and Bluetooth headset emissions of thermal radiation were analyzed and compared using a thermal imaging camera; this camera captured the local temperature around the ear-skull region.…”
Section: Bluetooth Hands-free Headsetssupporting
confidence: 52%
“…EMR is made up of RF and thermal radiation and it causes dielectric heating once it penetrates through human body tissue. The skin around the ear-skull area is very thin, so EMR is absorbed quite easily and is known to affect the human immune system (Mat et al, 2010). In the study performed by Mat et al (2010), they found that the specific absorption rate (SAR) was higher in cellphones that operated in higher frequencies (Mat et al compared cellphone frequencies of 900 MHz and 1800 MHz), as they produced higher levels of EMR.…”
Section: Electromagnetic Radiationmentioning
confidence: 99%
“…Ilvonen et al [24] analyzed the effect of magnetic field induced through GSM mobile phones was considerably lower than the basic restriction limit given. The biological effects of mobile phone radiations studied in literature includes anxiety, sleep disorders, memory loss, pain in ear and temperature rise [25] in surrounding nerves, complicated birth and miscarriages in case of pregnant woman, effect on eyes [26]. In contrast to the research on increase in the alpha band power, in 2007 Perentos et al [27] found no significant change in the alpha power due to mobile phone radiations.…”
Section: Related Studymentioning
confidence: 99%
“…EEG is due to the neural activation inside the brain that controls the functioning of the whole body system. EEG consists of five brain waves viz; delta (0.5-4 Hz), theta (4)(5)(6)(7)(8), alpha (8)(9)(10)(11)(12), beta1 (12)(13)(14)(15)(16)(17)(18)(19)(20), beta2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [9] and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Each wave can be termed as a clock signal for the other body organs for proper functioning and also for the synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few studies on determining these triggering causes, they have gained speed recently. There are scientific studies especially about the effect of electromagnetic waves emitted by mobile phones on human health [24]. The excessive use of smartphones is estimated to cause some organic and psychological health problems.…”
Section: Discussionmentioning
confidence: 99%